Population Pharmacokinetics of an Intranasally Administered Combination of Oxymetazoline and Tetracaine in Healthy Volunteers. (23rd August 2016) - Cacek, Anthony T.; Gobburu, Jogarao V. S.; Gopalakrishnan, Mathangi
Abstract: The primary objective of the current investigation was to establish the pharmacokinetic characteristics of oxymetazoline and tetracaine's primary metabolite, para ‐butylaminobenzoic acid (PBBA), after the intranasal administration of oxymetazoline/tetracaine. Thirty‐six subjects contributing a total of 1791 plasma concentration results from 2 open‐label trials were utilized. Model development was achieved using data from the second trial (N = 24) in which 0.3 mg oxymetazoline/18 mg tetracaine was administered. External model validation utilized data from the first trial (N = 12), which included doses of 0.3 mg oxymetazoline/18 mg tetracaine and 0.6 mg oxymetazoline/36 mg tetracaine. Oxymetazoline and PBBA dispositions were described by a 2‐compartment model with first‐order absorption. An allometric model for body weight was included on volumes and clearances to describe unexplained between‐subject variability. The final oxymetazoline parameter estimates were ka 4.41 h −1 ; peripheral volume 418 L; clearance 66.4 L/h; central volume 6.97 L; and intercompartmental clearance 419 L/h for a 70‐kg subject. The final PBBA parameter estimates were ka 8.51 h −1 ; peripheral volume 32.0 L; clearance 16.7 L/h; central volume 29.8 L; and intercompartmental clearance 2.43 L/h for a 70‐kg subject. Between‐subject variability ranged from 14% to 39% for oxymetazoline and from 10% to 94% for PBBA.